Odpowiedzi

2010-03-21T13:18:26+01:00
A) x/3+2=x /*3
x+6=3x
-2x=-6 /÷(-2)
x=3
b) -7(2x+1)=4
-14x-7=4
-14x=11 /÷/(-14)
x=-11/14
c)x/4- x-1/4=1/4 /*4
x-4x-1=1
-3x=2 /÷(-3)
x=-2/3
2010-03-21T13:21:32+01:00
A)
x/3+2=x|*3
x+6=3x
x-3x=-6
-2x=-6
x=3

b)
-7(2x+1)=4
-14x-7=4
-14x=4+7
-14x=11
x=-¹¹/₁₄

c)
x/4- x-1/4=1/4|*4
x-4x-1=1
-3x=1+1
-3x=2
x=-⅔
2010-03-21T13:22:16+01:00
A) x/3+2=x|*3
x+6=6x
-5x=-6|/(-5)
x=1,2
b) -7(2x+1)=4
-14x-7=4
-14x=11|/(-14)
x=-11/14
c)x/4-x-1/4=1/4|*4
x-4x-1=1
-3x=2|/(-3)
x=-2/3